Proceedings of the 35th Annual ACM Symposium on Applied Computing 2020
DOI: 10.1145/3341105.3373955
|View full text |Cite
|
Sign up to set email alerts
|

On the reliability of hardware event monitors in MPSoCs for critical domains

Abstract: Performance Monitoring Units (PMUs) are at the heart of most-advanced timing analysis techniques to control and bound the impact of contention in Commercial Off-The-Shelf (COTS) SoCs with shared resources (e.g. GPUs and multicore CPUs). In this paper, we report discrepancies on the values obtained from the PMU event monitors and the number of events expected based on PMU event description in the processor's official documentation. Discrepancies, which may be either due to actual errors or inaccurate specificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…-Device hardware architecture and component-specific (e.g., memory [70,43,68,101,109,104], cache [69,87,154,96,97,194]) -Exclusive access policies [96,97,194] -Software virtualization [84,114,141,41,174,112] -WCET analysis [48,29,30,85,33,16,90,89,88] -Execution time variability reduction and management [18,41,42,67,82,84,88,142,144,200,101,70,68,109,43,141,147,47,81,24] -Temporal diagnostics …”
Section: Temporal Interference and Spatial Interferencementioning
confidence: 99%
See 2 more Smart Citations
“…-Device hardware architecture and component-specific (e.g., memory [70,43,68,101,109,104], cache [69,87,154,96,97,194]) -Exclusive access policies [96,97,194] -Software virtualization [84,114,141,41,174,112] -WCET analysis [48,29,30,85,33,16,90,89,88] -Execution time variability reduction and management [18,41,42,67,82,84,88,142,144,200,101,70,68,109,43,141,147,47,81,24] -Temporal diagnostics …”
Section: Temporal Interference and Spatial Interferencementioning
confidence: 99%
“…The most relevant GPU device architectural components are described in Section 2.1 and Figure 1. Except for the SM, all described components are also common for multi-core devices: processing units (CPU cores, SMs), memory None [119,54,100,201]; ARM [12,14,34,40,47,162,15,25,32,39,47,105,142] Pascal None [12,14,13,16,40,169,39,96,81,120]; ARM [18, 9,…”
Section: Device Hardware -Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line, some authors already reported different observed behavior of the coherence protocol to that reported in the Technical Reference Manuals (TRMs) [12]. Others reported discrepancies in the hardware monitors between the observed values and the description provided in the TRM [1,11,16].…”
Section: Introductionmentioning
confidence: 97%
“…case in Table II (conclusion-L2A). A GetS/GetM message is sent for every address read or written by the DMAr1 . Hence, the number of expected ESR is 65,536 in (A) and (B) and 32,768 in (C) and (D), matching the observed results in TableII (M2S) (conclusion-ESR).…”
mentioning
confidence: 99%